A prospective observational cohort study of concomitant versus sequential phlebectomy for tributary varicosities following axial mechanochemical ablation. (October 2019) - Mohamed, Abduraheem; Leung, Clement; Hitchman, Louise; Wallace, Tom; Smith, George; Carradice, Daniel; Chetter, Ian
Introduction: Endovenous mechanochemical ablation (MOCA) is an increasingly popular non-thermal non-tumescent technique used to treat axial reflux in patients with superficial venous incompetence. However, the optimal management of varicose tributaries following this technique is unknown and may impact on patient outcomes. This study compares MOCA with concomitant phlebectomy (MOCAP) versus ablation with sequential phlebectomy if required (MOCAS). Methods: Patients with symptomatic Comprehensive Classification System for Chronic Venous Disorders (CEAP C2–C6) unilateral axial reflux were studied. Patient choice determined whether concomitant treatment of varicosities was carried out. The primary outcome was the Aberdeen Varicose Veins Questionnaire (AVVQ) at one year. Secondary outcomes included: Venous Clinical Severity Scores (VCSS), EuroQol 5-Domain quality of life scores, complications, procedure duration, procedural and post-operative pain scores and need for secondary procedures. Outcomes were assessed at baseline and then one week, six weeks, six months and one year post intervention. Results: Fifty patients underwent MOCAP and 33 patients MOCAS. The two groups were comparable at baseline. MOCAP was associated with lower (better) AVVQ scores at six weeks (3.4 (0.5–6.0) vs. 6.1 (1.8–12.1); P  = 0.009) and at six months (1.6 (0.0–4.5) vs. 3.34 (1.8–8.4); P  = 0.009) but by one year the difference was no longer statistically significant (1.81 (0.0–4.5) vs. 3.81 (0.2–5.3); P  = 0.099). MOCAP was associated with longer procedural duration (45 min (36–56) vs. 30 min (25–37); P  < 0.001) and higher maximal periprocedural pain (31 (21–59) vs. 18 (7–25); P  = 0.001). VCSS at all time points were lower in favour of MOCAP (0 (0–1) vs. 1 (0–3); P  < 0.001). MOCAP was associated with fewer episodes of clinically significant thrombophlebitis (6 of 50 (12%) vs. 10 of 33 (30%); P  = 0.039) and lower numbers of secondary procedures (2 (4%) vs. 6 (18%); P  = 0.032). Conclusion: Concomitant treatment of tributary varicosities following MOCA improves quality of life and clinical severity, while reducing rates of re-intervention and post-operative thrombophlebitis compared to sequential treatment. The penalty is a modest increase in procedural duration and discomfort. Further evidence from longer-term follow-up is needed.